2005
DOI: 10.1152/ajpregu.00858.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic denervation does not prevent a reduction in fat pad size of rats or mice treated with peripherally administered leptin

Abstract: . Sympathetic denervation does not prevent a reduction in fat pad size of rats or mice treated with peripherally administered leptin. Am J Physiol Regul Integr Comp Physiol 289: R92-R102, 2005; doi:10.1152/ajpregu.00858.2004.-Leptin increases sympathetic nervous system (SNS) activity in brown adipose tissue and renal nerves. Experiments described here tested whether SNS innervation is required for peripheral, physiological concentrations of leptin to reduce body fat. In experiment 1, one epididymal (EPI) fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 52 publications
1
53
1
Order By: Relevance
“…In addition, leptin and pair feeding had opposing effects on NETO in RP fat from the centrally infused animals. Because the size of all white fat depots except MES decreased in both the centrally leptininfused and pair-fed animals in experiment 3, these results indicate that leptin does not depend on the SNS to reduce the size of all fat depots, consistent with the results of a study in which rats with one sympathetically denervated fat pad were infused with leptin (34). The results from experiment 2 also support this conclusion because peripherally infused leptin caused a significant decrease in the size of the MES tissue, whereas ING fat was the only depot to show even a tendency for an increase in NETO.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In addition, leptin and pair feeding had opposing effects on NETO in RP fat from the centrally infused animals. Because the size of all white fat depots except MES decreased in both the centrally leptininfused and pair-fed animals in experiment 3, these results indicate that leptin does not depend on the SNS to reduce the size of all fat depots, consistent with the results of a study in which rats with one sympathetically denervated fat pad were infused with leptin (34). The results from experiment 2 also support this conclusion because peripherally infused leptin caused a significant decrease in the size of the MES tissue, whereas ING fat was the only depot to show even a tendency for an increase in NETO.…”
Section: Discussionsupporting
confidence: 84%
“…Few in vivo studies have examined the effect of leptin on the activity of sympathetic nerves in white fat depots (7,30,34), and, to our knowledge, a comparison of the effects of peripheral and central leptin infusion on NETO in individual fat depots has not previously been reported. We found that, regardless of the route of administration, leptin did not cause a uniform NETO response among the fat depots measured and that leptin decreased fat pad size independently of changes in NETO in several fat depots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 In addition, DMH NPY knockdown increased the gene expression of the 'thermogenic program' (that is, PPARĪ³ and Pgc-1Ī± mRNA) in IWAT 44 ; DWAT was not assayed. To demonstrate that this effect was dependent on the SNS innervation of WAT, they used our specific, unilateral sympathetic denervation model, [45][46][47][48] where one IWAT depot received intra-WAT injections of the noradrenergic toxin 6-hydroxy-dopamine (6-OHDA) and its within-animal contralateral IWAT mate received vehicle control injections. [45][46][47][48] In the neurally intact IWAT pads of DMH NPY knockdown rats receiving intra-WAT vehicle injections, NE content (often a surrogate used for sympathetic drive, but not a replacement for NE turnover) was significantly increased compared with that of separate control rats receiving DMH injection of the scrambled shRNA.…”
Section: Methodsmentioning
confidence: 99%
“…For example, fasting-induced decreases in WAT mass in laboratory rats, cats, rabbits, and dogs (110)(111)(112)(113)(114) are blocked, by surgical denervation, as is estradiol-induced decreases in WAT mass of ovariectomized rats (115) and the SD-induced decreases in WAT mass of Siberian hamsters (44,116,117). The lipidmobilizing effects of physiological doses of leptin given peripherally, however, are not blocked by WAT sympathetic denervation in laboratory rats (53).…”
Section: Wat Denervation Studies Provide Functional Evidence For the mentioning
confidence: 99%